2021
DOI: 10.13057/biodiv/d220902
|View full text |Cite
|
Sign up to set email alerts
|

The Fourier transform infrared spectroscopy from Diplazium esculentum and Rivina humilis analysis to reveals the existence of necessary components in oil palm plantations of Ganoderma boninense control

Abstract: Abstract. Saragih WS, Purba E, Lisnawita, Basyuni M. 2021. The Fourier transform infrared spectroscopy from Diplazium esculentum and Rivina humilis analysis reveals necessary components in oil palm plantations of Ganoderma boninense control. Biodiversitas 22: 3645-3651. The Fourier transform infrared spectroscopy (FTIR) has been widely utilized for biological samples and biomolecular characterization. We aim to identify Ganoderma boninense through FTIR and obtain a functional group that can facilitate early ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…It is possible that together with nitrogenous compounds, utilization of lipids may act as surface-stabilizing agents for achieving homogeneous and small size X-doped TiO 2 -NPs, also reported previously . The remaining two unaffected regions, i.e., 558–840 and 1900–2300 cm –1 , likely correspond to polyphenolic or nitrogenous compounds. Overall, the ATR-FTIR study of the SNS process revealed involvement of nitrogen- and carbon-related species during the reaction of Ti 3 (PO 4 ) 4 · x H 2 O with the extract. Thus, the synthesized materials should exhibit P, N, and C doping, which is further examined below.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…It is possible that together with nitrogenous compounds, utilization of lipids may act as surface-stabilizing agents for achieving homogeneous and small size X-doped TiO 2 -NPs, also reported previously . The remaining two unaffected regions, i.e., 558–840 and 1900–2300 cm –1 , likely correspond to polyphenolic or nitrogenous compounds. Overall, the ATR-FTIR study of the SNS process revealed involvement of nitrogen- and carbon-related species during the reaction of Ti 3 (PO 4 ) 4 · x H 2 O with the extract. Thus, the synthesized materials should exhibit P, N, and C doping, which is further examined below.…”
Section: Resultsmentioning
confidence: 92%
“… 49 The remaining two unaffected regions, i.e., 558–840 and 1900–2300 cm –1 , likely correspond to polyphenolic or nitrogenous compounds. 50 52 Overall, the ATR-FTIR study of the SNS process revealed involvement of nitrogen- and carbon-related species during the reaction of Ti 3 (PO 4 ) 4 · x H 2 O with the extract. Thus, the synthesized materials should exhibit P, N, and C doping, which is further examined below.…”
Section: Resultsmentioning
confidence: 93%
“…Peaks at 1259 cm -1 were associated with the asymmetric and symmetric stretching of P=O bonds in the phosphodiesters (Ahmed et al 2017). The peak at 1234 cm -1 was related to the C-O stretching (Roy et al 2015;Saragih et al 2021). A strong band at 1032 cm -1 was attributed to the S-O bond and C-N stretching in aliphatic amines (Stan et al 2015;Taranath et al 2015).…”
Section: Ftirmentioning
confidence: 99%